Patient Perception of Reimbursement for Arthroscopic Meniscectomy and ACL Reconstruction. Issue 7 (18th July 2016) - Okoroha, Kelechi; Keller, Robert A.; Marshall, Nathan E.; Guest, John-Michael; Lynch, Jonathan; Lock, Terrence R.; Rill, Brian K.
Objectives: Healthcare policy changes and decreases in Medicare physician reimbursement continue to change the landscape of healthcare. Historically, patient perceptions of surgeon reimbursement have been exaggerated compared to actual reimbursement. Currently there is limited evidence for patient perception for arthroscopic meniscectomy and ACL reconstruction. The purpose of this study was to evaluate patient perception of physician reimbursement for arthroscopic meniscectomy and ACL reconstruction and to compare health care perceptions between urban and suburban clinics. Methods: Surveys were given to 231 consecutive patients, 127 in an urban clinic and 104 in a suburban clinic. Patients were asked their estimation of reasonable reimbursement for arthroscopic meniscectomy and ACL reconstruction as well as their perception on actual Medicare reimbursement to physicians. They were also asked how much would they be willing to pay out of pocket for the procedures. After revealing actual reimbursement rates, patients were asked if reimbursement levels were appropriate, whether surgeon subspecialty training was important, and if additional compensation should be associated with subspecialty training. Survey responses were compared with respondents in an urban versus a suburban setting as well as amongst income and education level. Results: Patients on average reported surgeons should receive 8, 096 for a meniscectomy and 11, 794 for an ACL reconstruction, 14 times and 11 times as much as actually reimbursed, respectively. Patients estimated that Medicare paid physicians 5, 442 for a meniscectomy and 6, 667 for an ACL reconstruction. Patients were willing to pay 2, 286 out of pocket for a meniscectomy and 11, 793 for an ACL reconstruction. Sixty five percent of patients believed reimbursement for meniscectomy was too low and 57% of patients believe reimbursement for ACL reconstruction was too low. Less than 2% of patients believed physician salaries should be cut, whereas 75% believed physicians should be paid extra for sub-specialty training. There were no differences in payment perception between urban and suburban settings. Conclusion: Patients perceived the values of meniscectomy and ACL reconstruction were substantially higher than current Medicare reimbursement. Majority of patients believed that the current reimbursement is too low and patients on average would be willing to pay more out of pocket than is currently reimbursed.